Integration of Local Wisdom Values in Character Education: A Comparative Study between Indonesia and Malaysia - Khojir Khojir; Kamarul Azmi Jazmi; Rosita Rosita; Sudadi Sudadi; Agus Setiawan; Muhammad Zuhair Zainal (Tarbiyah Wa Ta'lim: Jurnal Penelitian Pendidikan dan Pembelajaran, 2025)
Character education has become a strategic focus in shaping the quality of young generations in Indonesia and Malaysia, particularly amid the challenges of globalization, urbanization, and Western cultural influences that erode moral values and cultural identity. This study aims to identify models and practices for integrating local wisdom into character education, as well as to analyze the similarities, differences, and contributions of these practices to the development of students’ character in both countries. The research employed a Systematic Literature Review (SLR) with a meta-synthesis approach to examine, evaluate, and synthesize qualitative research findings from accredited national and international journals (2019–2025). Fifteen articles met the final inclusion criteria (11 from Indonesia, 4 from Malaysia). The results indicate that: (1) In Indonesia, the integration of local wisdom values is implemented through curriculum, thematic learning, extracurricular activities, and habitual practices in daily life, whereas in Malaysia, integration occurs through specialized curricula, culturally-based instruction, and community education. (2) Similarities between the two countries lie in the role of local wisdom in strengthening moral, social, and religious character, while differences are found in cultural scope, curriculum focus, and language roles. (3) Integrating local wisdom significantly reinforces character education, fosters moral and social values, and preserves students’ cultural identity according to the national context of each country.